2010
DOI: 10.1001/archoto.2010.43
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke as a Potential Cause of Chronic Rhinosinusitis

Abstract: Exposure to SHS is common and significantly independently associated with CRS. These findings have important clinical and public health implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…Another factor which may contribute to the burden of SDB in lower SES populations is secondhand smoke exposure. Indeed, children exposed to second-hand smoke experience increased episodes of otitis media and respiratory disease [26]. Exposed children may experience adenoidal or nasal mucosal inflammation and sinusitis, leading to increased snoring and sleep disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor which may contribute to the burden of SDB in lower SES populations is secondhand smoke exposure. Indeed, children exposed to second-hand smoke experience increased episodes of otitis media and respiratory disease [26]. Exposed children may experience adenoidal or nasal mucosal inflammation and sinusitis, leading to increased snoring and sleep disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that active cigarette smoking is more prevalent among patients with CRS. [78, 79**, 80]. The GA 2 LEN determined that there is a strong association between CRS and active tobacco use (aOR=1.9, 95% CI: 1.8–2.1), with a significant, but smaller, association of CRS with former smokers (aOR=1.3, 95% CI: 1.2–1.4).…”
Section: Tobacco Exposurementioning
confidence: 99%
“…The few studies examining the relationship between second hand smoke exposure or environmental tobacco smoke (ETS) and adult CRS have produced conflicting results, while studies of CRS in children have demonstrated a consistent association between ETS and CRS among children who have had sinus surgery. [8083] Studies examining the pathophysiologic effects of tobacco smoke on sinonasal mucosa suggest the reported associations are biologically plausible given findings that smoke decreases the mucociliary clearance of sinonasal mucosa by altering ionic transport mechanisms, impairs ciliogenesis, and suppresses innate immunity through alterations in toll-like receptors (TLRs), effector proteins (eg, β-defensins) and complement components. [84, 85]…”
Section: Tobacco Exposurementioning
confidence: 99%
“…Normal mucociliary clearance requires an adequate permeability of the sinus ostium as well as good secretory and ciliary functions [10]. From a pathophysiological point of view, CMRS is due to a temporary and reversible mucociliary dyskinesia [11], which could be favoured by several factors: gastroesophageal reflux disease [12], atmospheric pollution [13], smoking [14], nasosinusal polyposis [15], arterial hypertension [15], dental infections, anatomic malformations such as septal deviations, concha bullosa, allergic reactions, and immune deficits [16–20]. Odontogenic CMRS occurs when the Schneiderian membrane is irritated or perforated, as a result of a dental infection, maxillary trauma, foreign body into the sinus, maxillary bone pathology, the placing of dental implants in the maxillary bone, supernumerary teeth, periapical granuloma, inflammatory keratocyst, or dental surgery like dental extractions or orthognathic osteotomies [3, 21].…”
Section: Introductionmentioning
confidence: 99%